Correlation between the electronic/local structure and CO-oxidation activity of PdxRu1−x alloy nanoparticles. Issue 2 (19th December 2018) - Song, Chulho; Tayal, Akhil; Seo, Okkyun; Kim, Jaemyung; Chen, Yanna; Hiroi, Satoshi; Kumara, L. S. R.; Kusada, Kohei; Kobayashi, Hirokazu; Kitagawa, Hiroshi; Sakata, Osami
Abstract : Enhanced CO oxidation activity of PdRu nanoparticles (NPs) at x = 0.5 is originated from the maximum localized disorder of Pd/Ru and the charge transfer from Pd to Ru occurs in the partial PdRu alloy. Abstract : Pd x Ru1− x nanoparticles (NPs) were observed to display enhanced CO oxidation activity with the maximum performance obtained at the composition x = 0.5. To unveil the origin of this superior CO oxidation activity, we investigated the local structure, valence state, and electronic properties of Pd x Ru1− x NPs using synchrotron-based X-ray techniques. Site specific information obtained from X-ray absorption fine structure (XAFS) spectroscopy revealed that the local disorder around Pd and Ru atoms and their valence state can be systematically tuned by varying the Pd composition. Furthermore, the XAFS results indicated a strong correlation among the structural and valence state and the observed CO oxidation catalytic properties of Pd x Ru1− x NPs. Hard X-ray photoelectron spectroscopy (HAXPES) analysis suggested that the capability of CO oxidation requires an optimum balance between the adsorption and desorption energy for CO adsorption and eventually conversion to CO2 . A comparison between the experimental valence band (VB) HAXPES spectra of Pd x Ru1− x NPs and the linear combination of VB HAXPES spectra of Pd and Ru NPs revealed that the charge transfer from Pd to Ru occurs in the Pd x Ru1− x alloy at intermediate compositions, causing electron enrichment of the Ru surface. In addition, the maximum red-shift in the edge-position relative to that of bulk Pd/Ru and high structural disorder were observed for the PdRu alloy at the intermediate composition. This coupled behavior of structure and electronic properties followed the experimental trend of CO oxidation activity in this system.